2021
DOI: 10.1182/bloodadvances.2020002993
|View full text |Cite|
|
Sign up to set email alerts
|

Essential role for Gata2 in modulating lineage output from hematopoietic stem cells in zebrafish

Abstract: The differentiation of hematopoietic stem cells (HSCs) is tightly controlled to ensure a proper balance between myeloid and lymphoid cell output. GATA2 is a pivotal hematopoietic transcription factor required for generation and maintenance of HSCs. GATA2 is expressed throughout development, but because of early embryonic lethality in mice, its role during adult hematopoiesis is incompletely understood. Zebrafish contains 2 orthologs of GATA2: Gata2a and Gata2b, which are expressed in different cell types. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 68 publications
0
31
0
Order By: Relevance
“…These observations are consistent with the recovery of HSPC development reported in fish with mutations in a conserved enhancer that drives endothelial expression of Gata2a ( Dobrzycki et al, 2020 ). Other recent studies have shown that initial specification and endothelial-to-hematopoietic transition of HSC is intact in Gata2b knockout animals ( Gioacchino et al, 2021 ). In our studies we demonstrated that Gata2b u 5008/u5008 mutants have normal vascular development but have a reduction in HSPCs in the aorta from 36 hpf.…”
Section: Discussionmentioning
confidence: 98%
“…These observations are consistent with the recovery of HSPC development reported in fish with mutations in a conserved enhancer that drives endothelial expression of Gata2a ( Dobrzycki et al, 2020 ). Other recent studies have shown that initial specification and endothelial-to-hematopoietic transition of HSC is intact in Gata2b knockout animals ( Gioacchino et al, 2021 ). In our studies we demonstrated that Gata2b u 5008/u5008 mutants have normal vascular development but have a reduction in HSPCs in the aorta from 36 hpf.…”
Section: Discussionmentioning
confidence: 98%
“…As an example, the use of a blocking antibody directed against DLL4 during AGM hematopoiesis has provided great insight; blocking DLL4 during IAHC formation greatly enhances IAHC size and to a lesser extent HSC activity [38]. Finally, perhaps we will be able to decipher the molecular programs that are driven by Notch to specify HSCs by mining the vast number of single cell RNA sequencing data [29,33,37,[143][144][145][146][147][148][149]. In this case, we can circumvent modulation of Notch activity and directly induce the desired downstream signaling.…”
Section: How Much Notch Activity Is Needed For Hscs?mentioning
confidence: 99%
“…Following injections, embryos were treated with 0.003% 1-phenyl-2-thiourea (PTU, Sigma) at 24 hpf and fixed overnight with 4 % paraformaldehyde (PFA) in phosphate-buffered saline (PBS) containing 3% sucrose at 33 hpf. In situ hybridization (ISH) for cmyb was performed as previously described (Gioacchino at al., 2021;Chocron et al, 2007). The cmyb probe was a gift from Roger Patient.…”
Section: Cmyb In Situ Hybridizationmentioning
confidence: 99%